2015
DOI: 10.3109/07420528.2015.1033425
|View full text |Cite
|
Sign up to set email alerts
|

Day and night shift schedules are associated with lower sleep quality in Evening-types

Abstract: Eveningness has been suggested as a facilitating factor in adaptation to shift work, with several studies reporting evening chronotypes (E-types) as better sleepers when on night shifts. Conversely, eveningness has been associated with more sleep complaints during day shifts. However, sleep during day shifts has received limited attention in previous studies assessing chronotypes in shift workers. Environmental light exposure has also been reported to differ between chronotypes in day workers. Activity is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
2
13
0
2
Order By: Relevance
“…As previously mentioned, it has been proposed that a better alignment of chronotype with rotating or night shift work may lead to less circadian disruption, and hence influence the association between PCa and night shift work [ 42 ]. Furthermore, evening types have been thought to adapt better to night shifts; however, evening types have also been shown to have poorer sleep quality for both day and night shifts [ 56 ]. This may explain our findings of an increased risk in those with an evening chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, it has been proposed that a better alignment of chronotype with rotating or night shift work may lead to less circadian disruption, and hence influence the association between PCa and night shift work [ 42 ]. Furthermore, evening types have been thought to adapt better to night shifts; however, evening types have also been shown to have poorer sleep quality for both day and night shifts [ 56 ]. This may explain our findings of an increased risk in those with an evening chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even when exposed to a wide range of schedules imposed by the rotating shift work, this group presented few oscillations in relation to the measured variables, which is probably explained by the better adaptability of the intermediate chronotype in in most of the working hours of this schedule, especially to work during the day and in evening shifts. Schmidt et al, (2012) and Martin et al, (2015) studies highlighted that workers with intermediate chronotype showed a better adaptationas less misalignment and loss displacement of sleep -both for morning shifts and night shifts compared to evening chronotypes (Martin et al,2015), as we found in this study. Previous studies have also suggested that workers with evening chronotypes tend to tolerate better night shifts and morning individuals present a higher level of circadian misalignment when submitted to night work schedules (Juda, Vetter and Roenneberg, 2013).…”
Section: Resultssupporting
confidence: 80%
“…O efeito isolado do trabalho em turnos sobre a vigilância psicomotora e sua interação com variáveis que conhecidamente deterioram o estado de alertacomo a obesidade e o cronotipo do indivíduo (MARTIN et al, 2015) tem sido pouco explorado na literatura. Sabe-se que indivíduos obesos tendem a apresentar valores de tempo de reação mais vagarosos e um maior número de lapsos de atenção ao longo do rodízio.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The reason of this phenomenon is unclear. However, considering that early morning awakening is one of cardinal symptoms of shift work disorder [5], workers with eveningness chronotype are possibly prone to have shift work disorder based on their low stability of sleep schedule [6,7]. In other words, although short-term adaptation of shift work increases along with the greater tendency toward eveningness, eveningness chronotype does not necessarily lead to long-term continuity of shift work.…”
mentioning
confidence: 99%